333 Translating evidence into practice; development of the know injury knowledge?HUB. (1st September 2016) - Wells, Venessa; Meade, Rachel; Sweeny, Roisin; Zen, Marc; Piazz, Megan De; Affric, Jennifer
Abstract : Background: Knowledge exchange portals are effective tools to exchange information, resources and connect practitioners. It is well established that public health policy and program design should be informed by evidence. Evidence informed practice utilises the best available knowledge of what works and why in the design and delivery of policies and programs. Accessing and exchanging knowledge between practitioners is essential to evidence selection. Problem: Formative evaluation identified the need for a platform for injury prevention practitioners to access and share evidence across Western Australia (WA). We present an overview of the development, implementation and evaluation of the Know Injury Knowledge Hub (KH). Results: The Know Injury team at the Injury Control Council of Western Australia (ICCWA) developed the KH with the support of the WA Department of Health. The purpose was to provide information, tools and training to enhance the capacity of injury prevention practitioners to deliver, evidence informed activities. The hub is built upon three pillars; Know, Learn, Connect and is underpinned by a public health approach to injury prevention. It builds practitioners' knowledge about injury topics, providing an understanding of the extent of the problem, determinants, effective strategies, current initiatives and key stakeholders in WA. It focuses on increasing practitioner skills in relation to health promotion planning, implementation and evaluation and provides opportunities for practitioners, particularly those who are geographically isolated to initiate and build networks and partnerships with other practitioners. Conclusion: Driven by principles of sharing and knowledge, the hub utilises discussion boards, blogs, networking opportunities and online chat to encourage knowledge exchange. The KH is a single point of access for people with an interest in injury prevention and community safety and provides support for the delivery of evidence informed initiatives.